Metodologi Penelitian: Analisis Konseptual untuk Memahami Hakikat, Tujuan, Prosedur, dan Klasifikasi Penelitian - Nur, Zulfikah; Sulaiman, Umar; Rahman, Ulfiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to explore the different types of research that can be used based on the research objectives to be achieved. This research is carried out through a literature study method which is part of a qualitative approach. The main sources of research data are books and scientific articles published in scientific journals and indexed by google scholar. The keywords used in the article data generation are